Ultraviolet light‐emitting‐diode irradiation inhibits TNF‐α and IFN‐γ‐induced expression of ICAM‐1 and STAT1 phosphorylation in human keratinocytes. Issue 10 (28th September 2015) - Kwon, Tae‐Rin; Oh, Chang Taek; Choi, Eun Ja; Kim, Soon Re; Jang, Yu‐Jin; Ko, Eun Jung; Suh, Daewoong; Yoo, Kwang Ho; Kim, Beom Joon
Abstract : Background and Objectives: Ultraviolet light‐emitting diodes (UV‐LEDs) are a novel light source for phototherapy. This research investigated the in vitro safety and efficacy of UV‐LEDs as a phototherapeutic device for atopic dermatitis (AD). Study Design/Materials and Methods: Human keratinocytes and fibroblasts were irradiated by UV‐LEDs with a center wavelength of 310 and 340 nm. We examined the effects of UV‐LED irradiation on the suppression of TNF‐α/IFN‐γ‐induced activation of STAT1 and ICAM‐1 and on NF‐κB expression; we used the following methods: cell viability assay, reverse transcription‐polymerase chain reaction, enzyme‐linked immunosorbent assay, Western blotting, and immunocytochemistry. Results: We observed anti‐inflammatory responses through the suppression of TNF‐α/IFN‐γ‐induced expression of TARC and MCP‐1/CCL2, IL‐1beta, IL‐6, and sICAM‐1 via blockage of ICAM‐1 activation and subsequent activation of STAT1 and NF‐κB. The results suggested that UV‐LED irradiation inhibited ICAM expression by suppressing TNF‐α/IFN‐γ‐induced NF‐κB activation in vitro . Conclusion: We concluded that novel UV‐LED (310 and 340 nm) modalities were effective for the treatment of AD and may be promising for the treatment of inflammatory skin diseases. Lasers Surg. Med. 47:824–832, 2015. © 2015 Wiley Periodicals, Inc.